ANALISIS PERBANDINGAN PEROLEHAN HAK ATAS TANAH DAN PEMBANGUNAN PERUMAHAN GRIYA PANIKI INDAH MANADO BERDASARKAN NILAI JUAL OBJEK PAJAK DAN PETAZONA NILAI TANAH - Muhammad ., Rangga; O. Esry.H. Laoh; Margaretha C. Ratulangi (AGRI-SOSIOEKONOMI, 2017)
The purpose of this research is (1) to compare tax revenue of BPHTB based on NJOP with ZNT Map. (2) to know the potential of revenue that can be improved based on ZNT Map. This research was conducted at Griya Paniki Indah Housing, Kecamatan Mapanget, Manado City. from July to October 2017. The study used a statistical analysis of the mean difference test. The data used in this study is secondary data in the form of price of land and building transactions that occurred in 2014 and 2015. Research results indicate that the amount of revenue BPHTB refers to NJOP PBB or transaction price on 300 samples at Griya Paniki Indah Housing is Rp. 1,200,274,450, while the amount of BPHTB receipts referring to ZNT Map is Rp. 1,630,663,000 in comparison between NJOP versus ZNT is 1: 1.36. To this difference, the potential for BPHTB increase based on ZNT Map in Griya Paniki Indah Housing is 35.86%, so that Land Value Zone Map can increase the amount of BPHTB Manado City revenue.